Variation in semantic priming across age groups: An AERP study. - Mehta, Jyutika; Jerger, James (International Journal of Audiology, 2014)
Objective: To study the semantic priming effect on words across the life span by means of auditory event-related potentials (AERPs). Design: Participants heard a series of three words (S1, S2, and S3). The task was to indicate whether S2 was in the same semantic category as S3. Semantic priming was quantified as the difference between AERPs to the second word when it was semantically related to the first word (S2-R) or unrelated to the first word (S2-UR). Interest was focused entirely on the processing negativity (PN) component of the AERP to S2. The purpose of S3 was to delay the task decision so that the LPC generated by the decision would not confound the measurement of the PN component to S2. Sample: Ten children (9-11 years), 11 young adults (20-30 years), and 10 seniors (60-70 years). Results: The semantic priming effect was evident in the difference between peak amplitude of the PN component of the AERP to S2R and S2UR in all three groups. Children showed a clear asymmetry favoring the left hemisphere. In young adults, the asymmetry still favored the left hemisphere, but the degree of asymmetry was less robust. In the case of seniors, the priming effect was greater over the right hemisphere. Conclusion: Results suggest that all age groups benefit from contextual support, as evidenced by the semantic priming effect. However, differences in hemispheric asymmetry of activation indicate that perhaps seniors may need to recruit additional, but somewhat different brain resources to manage otherwise largely automatic tasks.